Contemporary pollen spectra from the Natal Drakensberg and their relation to associated vegetation communities - Hill, Trevor Raymond (Rhodes University, Faculty of Science, Botany Department, 1993)
The research focuses on the contemporary pollen rain-vegetation relationship for vegetation communities within the Natal Drakensberg, a region which is recognized as having the potential for extensive palynological investigations. The objective was to investigate the fundamental assumption underlying palynology, viz: that the pollen rain of a particular region is indicative or representative of the existing vegetation of that region. If the modern pollen rain is indicative of and/or distinctive for a particular vegetation community then the principle of methodological uniformitarianism can be applied, which states that the present day patterns and relationships can provide a factual basis for the reconstruction of the past through the extrapolation of modern analogues backwards in time. A vegetation survey was conducted in thirteen communities identified as pertinent to the research and a two-year modern pollen rain sampling programme was carried out, using both surface soil and pollen trap samples as a means of recording and quantifying the pollen rain. Once the necessary sample preparation and pollen counts had been performed, descriptive and numerical/statistical methods were employed to determine and describe the existing pollen-vegetation relationship. Descriptive analysis of the data sets was carried out with the aid of spectra depicted as rotated bar graphs and representing the relative percentage frequencies of the collected/counted taxa. Annual and seasonal pollen influx values were calculated and presented. Analysis of variance was applied to test various hypotheses related to sampling strategy and pollen influx variation. Statistical methods employed were two-way indicator species analysis (a classification analysis technique), detrended correspondence analysis and principal components analysis (ordination techniques), canonical correlation analysis (for data set association) and multiple discriminant analysis (for determination of vegetation zonal indices). The latter technique allowed for the probability of modern analogues to be assessed which are necessary for accurate interpretation of fossil pollen assemblages if the assumption under investigation is correct. The findings of the study were that the modern pollen rain-vegetation assumption holds true. Recommendations are put forward regarding future contemporary pollen studies with regards to the number of soil and pollen trap samples required, the magnitude of the pollen count and the numerical/statistical techniques most appropriate to clearly interpret the results. The conclusions are that future fossil pollen spectra can be expected to provide a good indication of former regional vegetation patterns for the study region. The study has extended the limited understanding of the contemporary pollen rain-vegetation relationship in South Africa and enables the interpretation of fossil pollen spectra to be carried out with greater confidence. This in turn lends greater credibility to possible Quaternary environmental change models required to help understand present and possible future environmental change.
Keywords: Pollen -- South Africa -- KwaZulu-Natal; Palynology -- South Africa -- KwaZulu-Natal